Use of Preoperative Cervical Vascular Imaging in Patients With Velocardiofacial Syndrome and Velopharyngeal Dysfunction in the United Kingdom. (June 2020) - Fallico, Nefer; Timoney, Norma; Atherton, Duncan
Objective: In patients with velocardiofacial syndrome (VCFS), medial displacement of the internal carotid arteries (ICAs) may increase the risk of vascular injury during the surgical correction of velopharyngeal dysfunction (VPD). Some surgeons advocate the use of vascular imaging studies prior to surgery. Nevertheless, the role of preoperative imaging is still controversial. This study aimed to review the current practice of the UK cleft units and also examine our own practice at the Evelina London Children's Hospital in relation to children with VCFS undergoing speech surgery over the previous 7 years. Design: A questionnaire was sent to all UK cleft surgeons to enquire about the management and use of preoperative vascular imaging in patients with VPD and VCFS. A retrospective study was also conducted of the unit's 7-year series of patients with VPD and VCFS. Results: Thirty-four completed questionnaires were returned (response rate 100%). Most UK surgeons (73.5%) do not regularly order preoperative vascular imaging for patients with VCFS although some reportedly would consider it if a posterior pharyngeal wall pulsation was visible. In our unit, between 2013 and 2019, a total of 40 patients affected by VCFS have been assessed for VPD. A magnetic resonance angiography (MRA) was performed for 23 patients. Medial deviation of the ICAs was identified in 7 (30%) patients. Conclusions: The results of the national survey showed no consensus on routine use of preoperative vascular imaging. Our retrospective study showed a 30% prevalence of medialized ICAs in our patient cohort. In these patients, the MRA findings influenced the choice of speech surgery.